"Waiting to Fail" Redux: Understanding Inadequate Response to Intervention. (August 2014) - Al Otaiba, Stephanie; Wagner, Richard K.; Miller, Brett
This introduction to the special series provides an overview of the promise, and the ongoing challenges, related to Response to Intervention (RTI) as a means of both prevention and identification of reading disabilities. We conclude by describing the articles in this special series and considering their implications for future research.